The role of the observer in the Everett interpretation - Zeh, Heinz-Dieter (Neuroquantology, 2013)
The role attributed to the observer in various interpretations of quantum mechanics as well as in classical statistical mechanics is discussed, with particular attention being paid to the Everett interpretation. In this context, the important difference between â€œquasi-classicalâ€ (robust against decoherence) and â€œmacroscopicâ€ or â€œphysically givenâ€ (redundantly documented in the environment) is pointed out.
Gesehen am 27.07.2021